2015
DOI: 10.1007/s11356-015-5390-x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal accumulation in lizards living near a phosphate treatment plant: possible transfer of contaminants from aquatic to terrestrial food webs

Abstract: We investigated the accumulation of heavy metals in Bosk's fringe-toed lizards (Acanthodactylus boskianus) living in Gabès region (southeastern Tunisia), in relation to habitat, diet, and distance from the Gabès-Ghannouche factory complex of phosphate treatment. More specifically, we compared the concentrations of cadmium, lead, and zinc in the stomach contents and samples of the liver, kidney, and tail from lizards living in four sites corresponding to different combinations of habitat (coastal dunes vs backs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…2 suggests there is a strong relationship between sediment and snake liver concentrations within sites. These results are consistent with the general pattern of fauna contaminated by metals increases if the population is exposed to a source of contamination (Nasri et al 2017), in this case the sediment. Therefore, our results support the use of tiger snakes as a bioindicators of wetland ecosystem health based on (1) the evidence that they accumulate a range of metals, (2) their long life expectancy of up to 24 years (Fearn and Norton 2011), (3) their small home ranges (~0.05 km 2 ) (Butler et al 2005) especially in wetlands isolated by urbanisation, and (4) their high trophic position in the food chain as adults (thus being exposed to all of their prey's contaminants).…”
Section: Occurrence Of Contaminants In Snakessupporting
confidence: 90%
“…2 suggests there is a strong relationship between sediment and snake liver concentrations within sites. These results are consistent with the general pattern of fauna contaminated by metals increases if the population is exposed to a source of contamination (Nasri et al 2017), in this case the sediment. Therefore, our results support the use of tiger snakes as a bioindicators of wetland ecosystem health based on (1) the evidence that they accumulate a range of metals, (2) their long life expectancy of up to 24 years (Fearn and Norton 2011), (3) their small home ranges (~0.05 km 2 ) (Butler et al 2005) especially in wetlands isolated by urbanisation, and (4) their high trophic position in the food chain as adults (thus being exposed to all of their prey's contaminants).…”
Section: Occurrence Of Contaminants In Snakessupporting
confidence: 90%
“…Previous studies have shown high levels of heavy metals in the coastal sediments close to the industrial complexes [61][62]. Particularly high concentrations were recorded in the site where the effluents are released: Cd>100 µg l , and Cr 100-120 µg l -1 [59,61]. The most important Ni and Co concentrations were observed in station 1, situated close to the phosphoric acid and fertilizer plant.…”
Section: Origin Of Trace Element Loading In Surface Waters In Three Gmentioning
confidence: 89%
“…Station 28 was near the commercial harbor and belonged to GA with a high concentration of Zn. The Gabes region in southeastern Tunisia, is a polluted area where such a situation is expected to contribute to the transfer of heavy metals from the marine to the bordering terrestrial ecosystems [59]. This area is nowadays considered as a pollution hotspot mainly due to the operation of the Gabes-Ghannouch factory complex of phosphate treatment for acid and fertilizer production since the early 1970s [60].…”
Section: Origin Of Trace Element Loading In Surface Waters In Three Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Metals are known hazardous substances and have also been widely detected in various environmental media including air, water, soil/sediment, and food (Zheng et al, 2013). Metals can be transferred through food chains and accumulated in vital organs of the human body (Nasri et al, 2015). Heavy metal cadmium (Cd) is applied in electroplating, pigment manufacture, printing and photographic industries, alloy preparation, and Cd batteries.…”
Section: Introductionmentioning
confidence: 99%